Angiotensin-(1–7) Promotes Resolution of Eosinophilic Inflammation in an Experimental Model of Asthma - Magalhaes, Giselle S.; Barroso, Lívia C.; Reis, Alesandra C.; Rodrigues-Machado, Maria G.; Gregório, Juliana F.; Motta-Santos, Daisy; Oliveira, Aline C.; Perez, Denise A.; Barcelos, Lucíola S.; Teixeira, Mauro M.; Santos, Robson A. S.; Pinho, Vanessa; et al. (Frontiers in Immunology, 2018)
Defective apoptosis of eosinophils, the main leukocyte in the pathogenesis of asthma, and delay in its removal lead to lung damage and loss of pulmonary function due to failure in the resolution of inflammation. Here we investigated the ability of angiotensin-(1-7), a pivotal peptide of the renin-angiotensin system, to promote resolution of an allergic lung inflammatory response. Balb/c mice were sensitized and challenged with ovalbumin and treated with angiotensin-(1-7) at the peak of the inflammatory process. Bronchoalveolar lavage (BAL) fluid and lungs were collected 24h after treatment. Different lung lobes were processed for histology to evaluate inflammatory cell infiltration, airway and pulmonary remodeling, total collagen staining and measurements of (i) collagen I and III mRNA expression by qRT-PCR; (ii) ERK1/2, IκB-α and GATA3 protein levels by Western blotting; (iii) eosinophilic peroxidase activity. Total number of inflammatory cells, proportion of apoptotic eosinophils and immunofluorescence for caspase 3 and NF-κB in leukocytes were evaluated in the BAL. Mas receptor immunostaining was evaluated in mouse and human eosinophils. Engulfment of human polimorphonuclear cells (PMNs) by macrophages, efferocytosis, was evaluated in vivo. Angiotensin-(1-7) reduced eosinophils in the lung and in the BAL, increased the number of apoptotic eosinophils, shown by histology criteria and by increase in caspase 3 imunostaining. Further, angiotensin-(1-7) decreased NF-kB imunostaining in eosinophils, reduced GATA3, ERK1/2 and IκB-α expression in the lung and decreased pulmonary remodeling and collagen deposition. Importantly, angiotensin-(1-7) increased efferocytosis. Our results demonstrate, for the first time, angiotensin-(1-7) activates events that are crucial for resolution of the inflammatory process of asthma and promotion of the return of lung homeostasis, indicating angiotensin-(1-7) as novel endogenous inflammation-resolving mediator.